2022
DOI: 10.1097/phm.0000000000001964
|View full text |Cite
|
Sign up to set email alerts
|

African Americans and Women Have Lower Functional Gains During Acute Inpatient Rehabilitation After Hemorrhagic Stroke

Abstract: Objective: Intracerebral hemorrhage can lead to significant long-term disability. While research in stroke rehabilitation has focused primarily on ischemic strokes, identifying factors that impact recovery in patients with intracerebral hemorrhage is necessary. Our purpose is to identify factors, including racial and sex disparities, associated with functional outcomes in intracerebral hemorrhage patients after inpatient rehabilitation. Design: This was a retrospective analysis of consecutive patients with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We agree that early functional status is helpful in determining prognosis after stroke 1 . The admission and discharge FIM scores reported were obtained at inpatient rehabilitation and were not obtained during the acute hospitalization, as mentioned in the first line of “Outcome measures” in the Methods section of the article 2 . The primary focus of our manuscript was FIM efficiency.…”
mentioning
confidence: 86%
“…We agree that early functional status is helpful in determining prognosis after stroke 1 . The admission and discharge FIM scores reported were obtained at inpatient rehabilitation and were not obtained during the acute hospitalization, as mentioned in the first line of “Outcome measures” in the Methods section of the article 2 . The primary focus of our manuscript was FIM efficiency.…”
mentioning
confidence: 86%
“…We agree that early functional status is helpful in determining prognosis after stroke. 1 The admission and discharge FIM scores reported were obtained at inpatient rehabilitation and were not obtained during the acute hospitalization, as mentioned in the first line of "Outcome measures" in the Methods section of the article. 2 The primary focus of our manuscript was FIM efficiency.…”
Section: Authors' Replymentioning
confidence: 99%
“…W e have read with great interest the article entitled "African Americans and women have lower functional gains during acute inpatient rehabilitation after hemorrhagic stroke" by Somani et al 1 The authors retrospectively analyzed data from 59 patients with intracerebral hemorrhage (ICH) who underwent rehabilitation therapy in an inpatient rehabilitation facility using multiple linear regression model. They concluded that African Americans and female ICH patients presented significantly poorer functional improvement after acute inpatient rehabilitation.…”
mentioning
confidence: 99%
See 2 more Smart Citations